Procedures and applications of nondestructive testing - Davis, Wesley (New York : NY Research Press, 2015)
This book provides basic theoretical knowledge about NDT and also discusses its practical applications. Non-destructive testing (NDT) aids scientists to assess the structures and properties of the materials and components that they are using. NDT techniques and models are economical and guarantee the quality of engineered systems and products. NDT methods use various procedures ranging from several contact methods, such as eddy current, magnetic particle and liquid penetrant testing, to contact-less method, such as radiography, thermography, and shearography. The book also covers several latest developments and applications of this technique in different fields, including evaluation of civil structures and its application in medicine.